2004
DOI: 10.1111/j.1365-2095.2004.00301.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of replacement of dietary fish meal by meat and bone meal and poultry by-product meal on growth and feed utilization of gibel carp, Carassius auratus gibelio

Abstract: Triplicate groups of gibel carp Carassius auratus gibelio (initial body weight: 5.25 ± 0.02 g) were fed for 8 weeks at 20-25°C on five isonitrogenous (crude protein: 400 g kg )1 ) and isoenergetic diets (gross energy: 17 kJ g)1). Meat and bone meal (MBM) or poultry by-product meal (PBM) were used to replace fish meal at different levels of protein. The control diet contained fish meal as the sole protein source. In the other four diets, 150 or 500 g kg )1 of fish meal protein was substituted by MBM (MBM 15 , M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
71
3
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 24 publications
9
71
3
2
Order By: Relevance
“…the protein provided by fishmeal in diets for Nile tilapia fry. Similar results have also been reported in rainbow trout (Steffens, 1994), African catfish (Abdel-Warith et al, 2001), gibel carp (Yang et al, 2004), Australian snapper (Rawles et al, 2006), Blacksea turbot (Yigit et al, 2006) and tilapia (Yıldırım et al, 2009) without affecting growth. Turker et al (2005) indicated that up to 25% of the fishmeal protein can be replaced by poultry byproduct meal with no negative effects in black sea turbot performance.…”
Section: Resultssupporting
confidence: 76%
“…the protein provided by fishmeal in diets for Nile tilapia fry. Similar results have also been reported in rainbow trout (Steffens, 1994), African catfish (Abdel-Warith et al, 2001), gibel carp (Yang et al, 2004), Australian snapper (Rawles et al, 2006), Blacksea turbot (Yigit et al, 2006) and tilapia (Yıldırım et al, 2009) without affecting growth. Turker et al (2005) indicated that up to 25% of the fishmeal protein can be replaced by poultry byproduct meal with no negative effects in black sea turbot performance.…”
Section: Resultssupporting
confidence: 76%
“…18.27% without compromising the health or growth performance of the snapper, showing a capacity similar to that of other species, such as the red sea bream, gilthead seabream and humpback grouper, when fed diets with a high inclusion of PBM-FG. Likewise, freshwater species such as tilapia, gibel carp and mahseer were able to digest a diet with up to 100% inclusion of PBM without a significant reduction in growth performance (Nengas et al, 1999;Takagi et al, 2000;Yang et al, 2006;Shapawi et al, 2007;Ismail et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…There has been a considerable research effort towards utilization of less expensive renewable ingredients in fish diet formulations to alleviate problems related to shortage of quality fish meal (Pongmaneerat et al 1993, El Sayed 1994, Rangacharyulu et al 2003, Yang et al 2004, Mukhopadhyay and Mitra 2007. Fish offal, which is generated in large quantities on a daily basis in the urban and sub-urban markets in India, has immense potential to be used as a predominant nutrient source in fish diet formulations.…”
Section: Introductionmentioning
confidence: 99%